The Apathetic State and the Explosion of Public Sector Strikes in Peru - Salvador Florian, Renzo Vito (2025)
Traditionally, strikes in Peru have followed similar trends to economic cycles and have been led by workers' organizations in sectors such as mining and manufacturing. However, since 2017, public sector unions have begun to lead the three classic strike indicators: frequency, man-hours lost, and number of strikers. This research takes nationwide mobilizations as a case study and explains these changes in trends using the theoretical framework of the political opportunity structure. In particular, it argues that this rise in conflict originated in public administration due to the reform in the regulation of collective bargaining (openness or access to participation). At the same time, in the private sector, the variations are related to the support of the heads of administrative offices (availability of influential allies). To demonstrate this thesis, this paper combines the dogmatic analysis of the institutional framework regulating the right to strike in Peru, along with the analysis of data recorded in the statistical yearbooks of the Ministry of Labor and Employment Promotion and 406 files of strike proceedings initiated before the General Directorate of Labor from 2017 to 2022.